(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Learning vocabulary is essential in any language learning. Many students find the traditional vocabulary training method tiresome and unproductive since it frequently focuses on rote memorization and isolated word definitions. This article suggests that incorporating games into vocabulary instruction can revolutionize the learning process.